Developing a Local Culture-Based Microlearning Strategy to Improve University Students’ Conceptual Understanding and Problem-Solving Ability in Mathematics - Titi Pujiarti; Mulya Yusnarti; Anggun Puspitasari; Feby Feby (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This study aims to develop a Local Culture-Based Microlearning Strategy to enhance university students’ conceptual understanding and problem-solving ability in mathematics. Although microlearning has been widely recognized as an effective digital learning innovation, there remains a research gap in contextualizing this approach within local cultural frameworks to improve mathematical understanding at the higher education level. Grounded in constructivist and contextual learning theories, this study adopts a Research and Development (R&D) method using Thiagarajan’s 4D model (Define, Design, Develop, and Disseminate). The study involved 40 first-semester students of the Primary School Teacher Education Program (PGSD) at STKIP Yapis Dompu. The developed microlearning videos integrated Dompu’s local cultural elements to connect abstract mathematical concepts with students’ lived experiences. Data were analyzed through expert validation, student response questionnaires, and pretest–posttest comparisons using Normalized Gain (N-Gain) statistics. The expert validation yielded a mean score of 90.13%, categorized as Highly Valid, while student responses averaged 98.5% (Very Positive). The N-Gain analysis showed an average score of 0.7, indicating a moderate improvement in conceptual understanding and problem-solving ability. Theoretically, the findings demonstrate that embedding local culture within microlearning not only strengthens conceptual comprehension through contextual learning but also enhances cognitive engagement in mathematics. This study contributes to digital pedagogy by providing empirical evidence that culturally contextualized microlearning serves as an effective and feasible strategy for mathematics education in higher education.